Transformasi Digital melalui Teknologi Berkembang: Tinjauan Literatur terhadap Peluang dan Tantangan - Dunita Salsabila Assyifa; Muhammad Ikhsanul Iman (Yayasan Literasi Sains Indonesia, 2026)
Digital transformation has become an important strategy for organizations to improve efficiency, innovation, and competitiveness through the adoption of emerging technologies. Technologies such as Artificial Intelligence (AI), Internet of Things (IoT), Big Data Analytics, Cloud Computing, and Blockchain provide opportunities to optimize business processes, enhance service quality, and support data-driven decision-making. This study aims to analyze the role of emerging technologies in supporting digital transformation and identify the opportunities and challenges associated with their implementation. The research employs the Systematic Literature Review (SLR) method by examining scientific articles published between 2021 and 2025 from reputable academic databases. The findings indicate that emerging technologies can improve operational efficiency, accelerate information processing, foster innovation, and increase organizational productivity. However, digital transformation implementation still faces challenges, including data security and privacy concerns, workforce readiness, technology investment costs, limited digital infrastructure, and the need for adaptive regulations. Therefore, technological development, digital competency enhancement, and effective governance are essential to ensure sustainable benefits of digital transformation across various sectors.